Identification of gallic acid based glycoconjugates as a novel tubulin polymerization inhibitors. Issue 4 (11th December 2015) - Upadhyaya, Kapil; Hamidullah; Singh, Kartikey; Arun, Ashutosh; Shukla, Mahendra; Srivastava, Neetika; Ashraf, Raghib; Sharma, Abhisheak; Mahar, Rohit; Shukla, Sanjeev K.; Sarkar, Jayanta; Ramachandran, Ravishankar; et al.
Abstract : A novel class of gallic acid based glycoconjugates were designed and synthesized as potential anticancer agents. Abstract : A novel class of gallic acid based glycoconjugates were designed and synthesized as potential anticancer agents. Among all the compounds screened, compound2a showed potent anticancer activity against breast cancer cells. The latter resulted in tubulin polymerization inhibition and induced G2/M cell cycle arrest, generation of reactive oxygen species, mitochondrial depolarization and subsequent apoptosis in breast cancer cells. In addition, ultraviolet-visible spectroscopy and fluorescence quenching studies of the compound with tubulin confirmed direct interaction of compounds with tubulin. Molecular modeling studies revealed that it binds at the colchicine binding site in tubulin. Further, 2a also exhibited potent in vivo anticancer activity in LA-7 syngeneic rat mammary tumor model. Current data projects its strong candidature to be developed as anticancer agent.